Valorization of whey for green synthesis of carbon dots and their potential applications - Poonia, Amrita; Aguirre-Güitrón, Lizet; Iñiguez-Moreno, Maricarmen; Santa, Dushica (Emerald, 2025)
Purpose This paper aims to develop carbon dots using whey as a valuable resource and to create a sustainable and biocompatible nanomaterial with potential applications in a variety of fields owing to its unique optical properties and antimicrobial capabilities, which are frequently used as sensing agents for detecting specific molecules in food, environmental and biomedical applications. Versatility of carbon dots (CDs) allows the utilization of these dots for a wide range of applications in areas such as food safety, antibacterial properties, production of composite polymers for food packaging, treatment of different diseases and detection of food-borne pathogens. Owing to their high brightness, low toxicity and excellent biocompatibility, CDs have attracted significant interest in food safety. This is also a cutting-edge technology that bids new ideas for treating various diseases. Design/methodology/approach Literature review related to using whey as the carbon source for synthesis of CDs was collected and studied from different sources like Google Scholar, Research Gate, online journals available at library of Banaras Hindu University, Web of Science and Scopus. A database of more than 100 scientific sources from different sources was made as per the headings and sub headings of the paper. Findings Whey generated as a by-product from the cheese industry contained a good amount of carbon and nitrogen that can be used for the fabrication of CDs. CDs produced using whey exhibited great photostability, high sensitivity and outstanding biocompatibility and also showed that Fe3+ ions could be quickly, sensitively and extremely selectively detected in an aqueous solution of CDs, with a revealing limit of 0.409 µM in the linear range of 0–180 µM. CDs are a promising area of study to a key component of next-generation multifunctional nanomaterials, promoting creativity, sustainability and useful solutions across a variety of industries, including health care and energy. The susceptibility of S. typhimurium (Gram-negative) was found to be higher than that of L. monocytogenes (Gram-positive) bacteria with MIC and MBC of 500  and 1000 µL/mL, respectively. Originality/value Whey-derived CDs are an environmentally beneficial substitute for conventional additives and their biocompatibility guarantees that they adhere to food safety regulations. In light of the future, the green volarization of dairy waste for the synthesis of CDs is consistent with the increasing worldwide focus on environmental responsibility and sustainability.